A common misconception about the building of the Sakhalin’s treasury department - Bazilevich Evgeny M. (Архитектон)
The article analyzes widespread information about one of the famous monuments of urban planning and architecture in Sakhalin Island – the Treasury building in Alexandrovsk-Sakhalinsky in the light of the ongoing study of activities carried out by architects and engineers on the eastern outskirts of Russia in the second half of the 19th - early 20th century. The research material presented in the article, in particular, on the activities of the architects I. A. Charushin and I. S. Stepanov who worked on Sakhalin, give reason to believe that the Treasury building of Sakhalin Island, currently used as a House of Creativity, was built according to the design of the architectural engineer I. S. Stepanov.